Estimation of canopy photosynthesis in rice by means of daily increases in leaf carbohydrate concentrations - Conocono, E.A.; Egdane, J.A.; Setter, T.L. (Wiley, 1998)
Procedures for rapid measurement of canopy photosynthesis are needed because current methods are time consuming and labor intensive. Our objective was to demonstrate that daily increases in nonstructural carbohydrates of shoots provide a good estimate of daily canopy photosynthesis for rice (Oryza sativa L.). Four cultivars— ‘IR72’, ‘IR64’, ‘IR50’, and ‘YRL39’— were grown in the field on a verlic tropaquept clay soil. Canopy photosynthesis was measured in the field every 2 h from sunrise (0600 h) to sunset (1800 h) and plotted over time to determine daily photosynthesis. Increases in shoot nonstructural carbohydrates per day were calculated by subtracting sunrise concentrations from those at sunset. Highly significant positive relationships between daily canopy photosynthesis and irradiance (r2 = 0.999) and leaf soluble sugars and irradiance (r2 = 0.981) were observed. Coefficients of determination for relationships between daily canopy photosynthesis and daily increases in leaf soluble sugars were high (r2 = 0.987). Growth stage comparisons showed the highest coefficients of determination at panicle initiation because non‐structural carbohydrates in the shoot were dependent on canopy light interception and photosynthesis. Relationships during flowering were intermediate because the spikelet was the main carbon sink. Removal of panicles at flowering increased coefficients of determination to r2 = 0.8. Relationships among cultivars for daily irradiance versus daily canopy photosynthesis or daily increases in leaf soluble sugars had r2 values of 0.7 to 1.0. We conclude that measuring daily increases in leaf carbohydrates can provide a simple, rapid screening procedure for evaluating canopy photosynthesis in rice.